Glutamine enhances pneumococcal growth under methionine semi-starvation by elevating intracellular pH - Zhang, Chengwang; Liu, Juncheng; Liu, Xiaohui; Xu, Yueyu; Gan, Qingxiu; Cheng, Qinqian; Liu, Weiping; Gao, Xiangmin; Wu, Songquan (Frontiers in Microbiology, 2024)
Bacteria frequently encounter nutrient limitation in nature. The ability of living in this nutrient shortage environment is vital for bacteria to preserve their population and important for some pathogenic bacteria to cause infectious diseases.Usually, we study how bacteria survive after nutrient depletion, a total starvation condition when bacteria almost cease growth and try to survive. However, nutrient limitation may not always lead to total starvation. No exogenous supply of methionine results in growth attenuation of Streptococcus pneumoniae, a human pathogen. In this paper, we refer to this inhibited growth state between ceased growth under total starvation and full-speed growth with full nutrients as semi-starvation.Similar to total starvation, methionine semi-starvation also leads to intracellular acidification.Surprisingly, it is intracellular acidification but not insufficient methionine synthesis that causes growth attenuation under methionine semi-starvation.With excessive glutamine supply in the medium, intracellular methionine level was not changed, while bacterial intracellular pH was elevated to ~ 7.6 (the optimal intracellular pH for pneumococcal growth) by glutamine deamination, and bacterial growth under semi-starvation was restored fully. Our data suggest that intracellular acidification decreases translation level and glutamine supply increases intracellular pH to restore translation level, thus restoring bacterial growth. This growth with intracellular pH adjustment by glutamine is a novel strategy we found for bacterial adaptation to nutrient shortage, which may provide new drug targets to inhibit growth of pathogenic bacteria under semi-starvation.